Premotor cortex is critical for goal-directed actions - Gremel, Christina; Costa, Rui (Frontiers in Computational Neuroscience, 2013)
Shifting between motor plans is often necessary for adaptive behavior. When faced with changing consequences of one’s actions, it is often imperative to switch from automatic actions to deliberative and controlled actions. The presupplementary motor area (pre-SMA) in primates, akin to the premotor cortex (M2) in mice, has been implicated in motor learning and planning, and action switching. We hypothesized that M2 would be differentially involved in goal-directed actions, which are controlled by their consequences vs. habits, which are more dependent on their past reinforcement history and less on their consequences. To investigate this, we performed M2 lesions in mice and then concurrently trained them to press the same lever for the same food reward using two different schedules of reinforcement that differentially bias towards the use of goal-directed versus habitual action strategies. We then probed whether actions were dependent on their expected consequence through outcome revaluation testing. We uncovered that M2 lesions did not affect the acquisition of lever-pressing. However, in mice with M2 lesions, lever-pressing was insensitive to changes in expected outcome value following goal-directed training. However, habitual actions were intact. We confirmed a role for M2 in goal-directed but not habitual actions in separate groups of mice trained on the individual schedules biasing towards goal-directed versus habitual actions. These data indicate that M2 is critical for actions to be updated based on their consequences, and suggest that habitual action strategies may not require processing by M2 and the updating of motor plans.